2021
DOI: 10.3390/ijerph18157743
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Intention to Receive Vaccination against COVID-19 in Puerto Rico: An Online Survey of Adults

Abstract: We conducted an online survey among adults in Puerto Rico to identify factors associated with the intention to receive vaccination against COVID-19. Sociodemographic variables were analyzed independently for association with intent to receive vaccination. Significant associations were included in the multivariate logistic regression analysis. A total of 1016 responses were available for analysis. In the bivariate analysis, younger age, higher education, pre-COVID-19 employment, male sex, gay/bisexual identity,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…However, the different demographic characteristics meant that people held different cognitions of COVID-19 vaccination. Married residents paid more attention to vaccine knowledge for the consideration of their families, and people with different incomes and occupations took different attitudes towards their own health and the accessing of information [18], which was consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, the different demographic characteristics meant that people held different cognitions of COVID-19 vaccination. Married residents paid more attention to vaccine knowledge for the consideration of their families, and people with different incomes and occupations took different attitudes towards their own health and the accessing of information [18], which was consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…These findings align with a recent analysis of online surveys in Latin America which found that among 7,000 Puerto Rican respondents, COVID-19 vaccine intention was 85%, slightly higher than the average in the region (80%), 11 and with a report that found a vaccine intention among Puerto Ricans was 68% before vaccine availability. 21 We also found that most parents (96%) who would vaccinate themselves were also willing to vaccinate their children, which is consistent with a recent multistate survey found that parents’ willingness to vaccinate their children closely matched their vaccine intention. 22 …”
Section: Discussionsupporting
confidence: 88%
“…After the elimination of duplicate studies, we assessed the titles and abstracts of the 434 remaining studies, and 401 articles were eliminated because they did not match the selection criteria. A total of 33 studies were read in full-text and 19 studies were included in the qualitative synthesis and 18 in the quantitative synthesis [ 10 , 13 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. We did not include the study of Villareal-Garza et al in the meta-analysis of non-pregnant women, because the study population was specifically women with breast cancer whereas the population of the remaining articles was made up of individuals without a specific pathology.…”
Section: Resultsmentioning
confidence: 99%